Szanse i zagrożenia aplikacji współczesnych koncepcji i metod zarządzania - Skalik, Jan (Chances and threats of application of contemporary concepts and management methods, 2005)
Applying contemporary concepts of management is a source of great advantages but it also has negative effects. The article presents their importance on the example of practices connected with the use of reengineering, lean management and outsourcing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 91-96